How Much Energy Do E'Athletes Use during Gameplay? Quantifying Energy Expenditure and Heart Rate Variability Within E'Athletes - Mitchell Nicholson; Dylan Poulus; Rob Robergs; Vincent Kelly; Craig McNulty (SpringerOpen, 2024)
Abstract Background Research into esports suggests that e'athletes experience physiological stressors and demands during competition and training. The physiological demands of esports are poorly understood and need to be investigated further to inform future training guidelines, optimise performance outcomes, and manage e'athlete wellbeing. This research aimed to quantify the metabolic rate of esports gameplay and compare this outcome with heart rate variability within expert e'athletes. Results Thirteen healthy male participants ranked within the top 10% of their respective esports title participated in the study (age = 20.7 ± 2.69 years; BMI = 24.6 ± 5.89 kg·m− 2). Expired gas analysis indirect calorimetry measured gas exchange during rest and gaming. Compared to resting conditions, competitive esports gameplay significantly increased median energy expenditure (1.28 (IQR 1.16-1.49) kcal·min− 1 vs. 1.45 (IQR 1.20-1.77) kcal·min− 1, p = .02), oxygen consumption (0.27 (IQR 0.24-0.30) L·min− 1 vs. 0.29 (IQR 0.24-0.35) L·min− 1, p = .02) and carbon dioxide production (0.20 (IQR 0.19-0.27) L·min− 1vs. 0.27 (IQR 0.24-0.33) L·min− 1, p = .01). Competitive gameplay also resulted in a significant increase in heart rate (84.5 (IQR 74.1-96.1) bpm vs. 87.1 (IQR 80.3-104) bpm, p = .01) and decrease in R-R interval's (710 (IQR 624-810) ms vs. 689 (IQR 579-747) ms, p = .02) when compared to rest. However, there were no significant differences in time or frequency measures of heart rate variability. Conclusions The data reveal increased physiological responses to metabolic rate, energy expenditure and cardiovascular function to esports game play within expert e'athletes. Further physiological research into the physical demands on e'athletes, the influence of different training programs to esport performance, and the added multivariate determinants to elite level esport performance are warranted.